Urgensi Pengenalan Konsep Literasi Numerasi pada Anak Usia Dini - Rahmadeni, Fevi; Arza Lia Citra; Zaskia Herawati; Purnamasari (ARITHMETIC: Academic Journal of Math, 2022)
This study discusses the urgency of introducing the concept of numeracy literacy in early childhood. Numerical literacy is one of the most needed skills in facing the 21st century, especially for the young generation. The question still remains, when should these skills be introduced and trained to the young generation candidates. Should it be introduced and taught from an early age? The purpose of this study was to determine the urgency of introducing the concept of numeracy literacy in early childhood. This study uses a literature review method where the authors collect 7 studies related to numeracy literacy in early childhood. From the results of the review that the author conducted on the seven related articles, there are 3 (three) important reasons why numeracy literacy should be introduced to early childhood. Based on these reasons, the authors conclude that the urgency of introducing the concept of literacy to early childhood is quite high, because numeracy literacy is a basic skill that must be possessed in the 21st century and early childhood is a golden age where the level of intellectual maturity of children is formed up to 80%.